KUALITAS AIR IRIGASI DI DESA AIR HITAM KECAMATAN LIMAPULUH KABUPATEN BATUBARA - Ivan Liharma Sinaga; Jamilah Jamilah; Mukhlis Mukhlis (Jurnal Agroekoteknologi, 2013)
ABSTRACTThe objective of this survey is to determine the value of the quality of irrigation water in the villageof Air Hitam in accordance with the value of irrigation water quality by U.S. Salinity LaboratoryStaff, 1954 and Ayers and Westcot, 1985. The research was conducted at the village of Air Hitam,Lima Puluh Subdistric, Batubara Distric, at the geographical of 03022'50" - 03023'6" N and 99050'34"- 99050'24" E. The results of the survey showed that the value of N, P dan Na irrigation water in thevillage of Air Hitam qualifies as irrigation water according to the standard value of Ayers andWestcot, 1985. DHL and SAR values of irrigation water before fertilizing to meet the irrigationwater standards as U.S. Salinity Lab staff.